A criança e a infância nos documentos da ONU: a produção da criança como 'portadora de direitos' e a infância como 'capital humano do futuro' - Oliveira, Fabiana de (Universidade Federal de São Carlos, 2008)
The developed research is characterized as a documental base study of a qualitative nature related to the United Nations (UN) and to the idea of child and childhood produced by this agency. The relevance to the development of the investigation is based on the importance of this agency in the production of new senses about the child and the childhood in the legal field, resulting in a transference of the childhood sense produced in the 18th century by the historical discourse as well as by the limitation of works involving this knowledge area. The research objectives were: to analyze the senses NU constructed along its existence about the idea of childhood; to investigate the produced conception of child and childhood; to explore and analyze the UN s practices related to the idea of childhood present in the documents. The research was developed considering the analysis of the three following documents produced by UN: The Genebra Declaration of 1924, The Child Rights Declaration of 1959 and the Convention on Child Rights of 1989. Peharps, the NU s documents do not point exactly to a conception of child and childhood, but they certainly give us clues of how the child and childhood, derived from this, should be transformed. UN is being understood as a dispositive of government concerning the children as a specific population managed by both the biopower and the norm that use the Right and its legal discourse (materialized through the Declarations for the children) to rule, control and produce its legal discourse in the contest for the production of the truth on childhood. The comprehension of the notion of Right is being understood based on Foucault, not as something strictly linked to the legal aspect, but considering a widest perspective which associates it to the norm. The child who bears rights and the childhood, as human capital of the future , will de considered as the effect of an intricate net of powers that confer it a given place, a subjectiveness and practices that govern it.
Keywords: Direitos das Crianças; Organização das Nações Unidas; Direito; Política; Infância; Crianças; NU; Right; Politics; Childhood; Child; CIENCIAS HUMANAS::EDUCACAO